Analisis Kualitas Pelayanan dan Pengaruhnya terhadap Loyalitas Pelanggan: Studi Kasus pada PT Pos Indonesia (Persero) Kantor Pos Sleman - Larasati, Rian; Supinardi, ,Bambang; Fadhilah, Muinah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The research aim to examine the influence of service quality’s variables (i.e. tangibles, reliability, responsiveness, assurance, and empathy) on customer loyalty. Multiple linear regression method, F-test and t-test were used to analyze data. The results proved the tangibles, reliability, responsiveness, assurance and empathy variables of service quality were significantly influenced the customer loyalty at PT. Pos Indonesia(Persero) Kantor Pos Sleman, both simultaneously and partially. Furthermore, the reliability variable of service quality was identified dominantly influence the customer loyalty. Keywords: Service quality, tangibles, reliability, responsiveness, assurance, emphaty, customer loyalty.